Homicide and gun control: the Brady Handgun Violence Prevention Act and homicide rates - Monroe, Jeffrey D. (Criminal justice recent scholarship, 2008)
Analyzing the impact of the Brady Bill on homicide rates -- The importance of gun control research -- An empirical test of the Brady Bill -- Failing to reduce handgun homicide rates -- Guiding policy with empirical evidence